Dominance hierarchy in different stages of development in colonies of the primitively eusocial wasp Mischocyttarus cassununga (Hymenoptera, Vespidae) - Prezoto, Fábio; Vilela, Ana P. P.; Lima, Maria A. P.; D'Ávila, Sthefane; Souza Sinzato, Danielle M.; Andrade, Flávio R.; Santos-Prezoto, Helba H.; Giannotti, Edilberto [UNESP] (My University, 2004)
Seven colonies of Mischocyttarus cassununga were studied under field conditions at Universidade Federal de Juiz de Fora, MG, in southeastern Brazil: in pre-emergence, post-emergence and decline stages, during 145.8 hours. Dominance interactions among the females were quantified to verify the dynamics of succession in the social hierarchy of the colonies. Early pre-emergence colonies present more intense aggressive interactions than late pre-emergence ones, because the females are engaged in securing the role of main egg layer in the nest. In post-emergence (pre-male) colonies the dominance hierarchy is more defined and the frequency of dominance and subordination behaviors were lower than in pre-emergence stages: most of the agonistic behaviors are restricted to the first ranked females (potentially queens) and the subordinate individuals play the role of workers in the nests. In the post-emergence, post-male, and decline stages the hierarchy is still maintained by the aggressive behaviors of the 1st-ranked female but because the presence of males and future nest foundresses these interactions are not well defined in a linear way.
Keywords: Aggressive behaviors; Colony stages; Hierarchy of dominance; Mischocyttarus cassununga; Vespidae; Hymenoptera; Mischocyttarus